Prostaglandin E2 Inhibits BMP Signaling and Delays Chondrocyte Maturation - Clark, Christine A. (2009)
While cyclooxygenases are important in endochondral bone formation during fracture healing, mechanisms involved in prostaglandin E2 (PGE2) regulation of chondrocyte maturation are incompletely understood. The present study was undertaken to determine if PGE2 effects on chondrocyte differentiation are related to modulation of the BMP signaling pathway. In primary murine sternal chondrocytes, PGE2 differentially regulated genes involved in differentiation. PGE2 induced type II collagen and MMP-13, had minimal effects on alkaline phosphatase, and inhibited the expression of the maturational marker, type X collagen. In BMP-2 treated cultures, PGE2 blocked the induction of type X collagen. All four EP receptors were expressed in chondrocytes and tended to be inhibited by BMP-2 treatment. RCJ3.1C5.18 chondrocytes transfected with the Protein Kinase A (PKA) responsive reporter, CRE-luciferase, showed luciferase induction following exposure to PGE2, consistent with activation of PKA signaling and the presence of the EP2 and EP4 receptors. Both PGE2 and the PKA agonist, dibutyryl cAMP, blocked the induction of the BMP-responsive reporter, 12XSBE, by BMP-2 in RCJ3.1C5.18 chondrocytes. In contrast, PGE2 increased the ability of TGF-β to activate the TGF-β-responsive reporter, 4XSBE. Finally, PGE2 down regulated BMP-mediated phosphorylation of Smads 1, 5, and 8 in RCJ3.1C5.18 cells and in primary murine sternal chondrocytes. Altogether, the findings show that PGE2 regulates chondrocyte maturation in part by targeting BMP/Smad signaling and suggest an important role for PGE2 in endochondral bone formation.